THE EFFECT OF GARLIC WATER EXTRACT (Allium sativum) THROUGH DRINKING WATER ON PROTEIN, FAT AND CHOLESTEROL CONTENTS OF THE LOHMANN BROWN YOLKS - N. M. R., Astiari; Bidura, I G. N. G.; Warmadewi, D. A. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
Nutrition in eggs is very important to know to improve the public health. This study aims to determine the effect of the level of extract of garlic water (Allium sativum) on protein, fat and cholesterol contents of laying chicken eggs of Lohmann Brown aged 22-30 weeks. This research was conducted for 3 months at laying chicken farm in Dajan Peken Village, Tabanan Subdistrict, Tabanan Regency. 36 laying chickens of Lohmann Brown with a homogeneous weight were raised in 18 squares of colony batray cages. The design used in this study was a complete randomized design (RAL) with 3 treatments and 6 replications.The treatment consisted of drinking water without additional garlic water extract (B0) as control, drinking water with 3% extract of garlic water (B1), and drinking water with additional garlic extract of 6% (B2). The variables observed in this study were dry weight of egg yolks, egg yolk protein content, fat content and yolk cholesterol content. The results showed that on treatment of B1 and B2 significantly (P <0.05) increased the yolk protein content compared with B0 as the control.  But in  the fat content and yolk cholesterol decreased compared with chicken that was not given garlic water extract (Allium sativum) B0 as control. From the results of this study, it can be concluded that the giving of garlic extract (Allium sativum) with 3% level and 6% through drinking water can increase protein content and decrease fat content and cholesterol of chicken egg yolks of Lohmann Brown aged 22-30 weeks. Keywords: Lohmann Brown chicken, egg yolk, and garlic water extract.